2000
DOI: 10.1590/s1516-31802000000100003
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors in non-Hodgkin lymphomas

Abstract: The intermediate grade lymphomas were more compatible with data found in the literature, probably because of the larger number of patients. In this specific case, the treatment did not have an influence on the survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
(29 reference statements)
1
2
1
1
Order By: Relevance
“…When patients were evaluated as over 60 and under 60 years old in two groups, it was found that older age in patients with NHL has an unfavourable impact on OS but had no effect on OS in patients with HL. No statistically significant effect of gender on prognosis and overall survival in lymphoma was reported in previous studies (9,11,4,18). In our study, as consistent with the relevant literature, no significant correlation was found between gender and mortality and OS in patients with HL and in patients with NHL.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…When patients were evaluated as over 60 and under 60 years old in two groups, it was found that older age in patients with NHL has an unfavourable impact on OS but had no effect on OS in patients with HL. No statistically significant effect of gender on prognosis and overall survival in lymphoma was reported in previous studies (9,11,4,18). In our study, as consistent with the relevant literature, no significant correlation was found between gender and mortality and OS in patients with HL and in patients with NHL.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, no significant correlation was found between the NLR and mortality and OS in patients with HL and in patients with NHL. A relation between a high LDH level and worse outcome for lymphoma has very often been demonstrated (8,4,13,18,24). No significant correlation was found between the LDH level and mortality and OS in patients with HL and in patients with NHL in our study.…”
Section: Discussioncontrasting
confidence: 71%
“…Indeed, blacks have a higher risk than whites [48,49], which is coherent with the ndings of our study. However, only a few reports of the association between yellows and disease are available in the literature [50,51]. The effect of the level of yellows on the survival of LGGs was similar according to survival models.…”
Section: According To Our Nomograms Age At Diagnosis Was Con Rmed Asmentioning
confidence: 85%
“…interstitial, focal and diffuse can be seen either alone or in combination. 6 , 7 Patients at high risk for failure with conventional therapy may benefit from investigational approaches. The biological markers of NHL are distinguished in three categories: serological, immunophenotypic and molecular markers.…”
Section: Introductionmentioning
confidence: 99%